2001
DOI: 10.1161/hs1101.098369
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Decompressive Craniectomy and Mild Hypothermia Ameliorates Infarction Volume After Permanent Focal Ischemia in Rats

Abstract: Background and Purpose-Both hypothermia and decompressive craniectomy (DC) have been shown to reduce ischemic injury in experimental middle cerebral artery (MCA) infarction. This study was designed to evaluate the effect of combined DC and hypothermia on infarction size and neurological outcome in a rat model of MCA occlusion (MCAO). Methods-MCAO was performed in 72 Wistar rats assigned to groups A through F. In group A, mild hypothermia (32°C) was induced 1 hour after MCAO for 5 hours; normothermia was mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 48 publications
4
33
1
1
Order By: Relevance
“…Reduced infarct volumes in the glibenclamide-treated groups, however, were often associated with marked sparing of the cerebral cortex (Fig. 5c,d), a phenomenon previously reported with decompressive craniectomy 19 .…”
Section: Glibenclamide Treatment In Thromboembolic Modelsupporting
confidence: 74%
“…Reduced infarct volumes in the glibenclamide-treated groups, however, were often associated with marked sparing of the cerebral cortex (Fig. 5c,d), a phenomenon previously reported with decompressive craniectomy 19 .…”
Section: Glibenclamide Treatment In Thromboembolic Modelsupporting
confidence: 74%
“…A definite decrease in the infarction size was not determined only in the 6-hour hypothermia group; however, it was found that hypothermia performed together with DC was more beneficial in decreasing the ischemic infarction size. When the result of the study by Doerfler et al [24] was compared with that of the present study, it was 11.8% and 10.6%, respectively, in the craniectomy groups. Moreover, as compared with the infarction ratio of 9.10% in the craniectomy+hypothermia group in the study by Doerfler et al, [24] the present study determined a similar infarction ratio of 9.7% in the DC+MAN group.…”
Section: Discussionsupporting
confidence: 39%
“…In previous studies, either the outcomes of very early period (first 6 hours) or at the 36 th and 72 nd hours have been discussed and sacrificing performed. [21][22][23][24] Bederson et al [10] have stated that TTC is a rapid, reliable, cheap, easily detectable, and convenient substance in demonstrating infarction area in the screening and recognition of cerebral infarction in rats. In the present study, we used TTC, as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is at least doubtfull however that it could reduce definite infarction size or improve neurological outcome. Hypothermia is probably less effective than decompressive craniectomy, but it may have an addictive role to surgery 8 . Although feasible, blanket cooling is associated with a number of severe complications including bleeding diathesis, arritmias and cardiac failure and uncontrolled intracranial hypertension during rewarming 7 .…”
Section: Discussionmentioning
confidence: 99%